Work, Poverty and Lack of Protection: The Working-age Population at the Center of the Debate in Argentina (2016-2022) - Costa, María Ignacia; Rottenschweiler, Sergio (Journal Studies of Public Policy, 2024)
This article examines the living and protection conditions of the working-age population during the pandemic and post-pandemic periods, along with debates regarding the implementation of alternative income guarantee policies. It highlights that income deterioration and insufficiency affect not only the most vulnerable workers, such as the unemployed and informal workers, but also those with formal salaried jobs. Currently, having formal employment does not guarantee freedom from poverty. During the pandemic, state intervention through income guarantee measures played a critical role in mitigating poverty. However, these measures were not sustained in the post-pandemic period due to emerging fiscal constraints. The analysis relies on secondary data from the Ministerio de Trabajo, Empleo y Seguridad Social (MTEySS) and the Instituto Nacional de Estadísticas y Censos (INDEC), as well as a review of newspaper records reflecting debates on protection gaps and the demands voiced by various worker groups. The study underscores the urgency of addressing these issues to ensure decent living conditions for the working population.